P-hydroxybenzaldehyde protects Caenorhabditis elegans from oxidative stress and β-amyloid toxicity - Yu, Xingzhi; Tao, Jie; Xiao, Tian; Duan, Xiaohua (Frontiers in Aging Neuroscience, 2024)
Introduction Gastrodia elata is the dried tuber of the orchid Gastrodia elata Bl. It is considered a food consisting of a source of precious medicinal herbs, whose chemical composition is relatively rich. Gastrodia elata and its extracted fractions have been shown to have neuroprotective effects. P-hydroxybenzaldehyde (p-HBA), as one of the main active components of Gastrodia elata, has anti-inflammatory, antioxidative stress, and cerebral protective effects, which has potential for the treatment of Alzheimer’s disease (AD). The aim of this study was to verify the role of p-HBA in AD treatment and to investigate its mechanism of action in depth based using the Caenorhabditis elegans (C. elegans) model. Methods In this study, we used paralysis, lifespan, behavioral and antistress experiments to investigate the effects of p-HBA on AD and aging. Furthermore, we performed reactive oxygen species (ROS) assay, thioflavin S staining, RNA-seq analysis, qPCR validation, PCR Array, and GFP reporter gene worm experiment to determine the anti-AD effects of p-HBA, as well as in-depth studies on its mechanisms. Results p-HBA was able to delay paralysis, improve mobility and resistance to stress, and delay aging in the AD nematode model. Further mechanistic studies showed that ROS and lipofuscin levels, Aβ aggregation, and toxicity were reduced after p-HBA treatment, suggesting that p-HBA ameliorated Aβ-induced toxicity by enhancing antioxidant and anti-aging activity and inhibiting Aβ aggregation. p-HBA had a therapeutic effect on AD by improving stress resistance, as indicated by the down-regulation of NLP-29 and UCR-11 expression and up-regulation of PQN-75 and LYS-3 expression. In addition, the gene microarray showed that p-HBA treatment played a positive role in genes related to AD, anti-aging, ribosomal protein pathway, and glucose metabolism, which were collectively involved in the anti-AD mechanism of p-HBA. Finally, we also found that p-HBA promoted nuclear localization of DAF-16 and increased the expression of SKN-1, SOD-3, and GST-4, which contributed significantly to inhibition of Aβ toxicity and enhancement of antioxidative stress. Conclusion Our work suggests that p-HBA has some antioxidant and anti-aging activities. It may be a viable candidate for the treatment and prevention of Alzheimer’s disease.